2008
DOI: 10.1002/macp.200800096
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of α‐Amino Acid N‐Carboxyanhydride (NCA) Polymerization by Capillary Electrophoresis

Abstract: Polymerizations of Nε‐trifluoroacetyl‐L‐lysine N‐carboxyanhydride initiated by hexylamine were performed in N,N‐dimethylformamide with different monomer to initiator ratios and at different temperatures. Poly(Nε‐trifluoroacetyl‐L‐lysine) samples were characterized by size exclusion chromatography coupled with multi‐angle laser light detection (SEC‐MALLS) and capillary electrophoresis (CE). If SEC‐MALLS analysis emphasizes the double distribution in molecular weight, nonaqueous CE (NACE) brings additional quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…The PBA‐Hs that we obtained from the HEX‐initiated Asp NCA polymerizations at room temperature had lower molar‐mass averages than predicted from the [M]:[I] ratios (50, 100, 200), but the results are in agreement with the trend of $\overline {M} _{{\rm n}} $ increase with the increasing [M]:[I] ratios (Table 1). Longer times were avoided to minimize the chain‐terminating reactions 19, 20, 22. By doubling the [M]:[I] ratio, a practically doubled molar‐mass average was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PBA‐Hs that we obtained from the HEX‐initiated Asp NCA polymerizations at room temperature had lower molar‐mass averages than predicted from the [M]:[I] ratios (50, 100, 200), but the results are in agreement with the trend of $\overline {M} _{{\rm n}} $ increase with the increasing [M]:[I] ratios (Table 1). Longer times were avoided to minimize the chain‐terminating reactions 19, 20, 22. By doubling the [M]:[I] ratio, a practically doubled molar‐mass average was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Control over the NCA polymerizations can only be achieved by keeping the polymer NH 2 end‐group as the only initiating species. Using capillary electrophoresis it was demonstrated by Vayaboury et al19, 20 that by lowering the reaction temperature to 0 °C, NH 2 end‐groups remain present for 99% of the polypeptide chains. It was suggested that the reactions of end‐groups with N,N ‐dimethylformamide (DMF) forming formamide‐terminated dead polypeptide chains are more pronounced at higher reaction temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45][46] Alternatively, the polymerization of MES-L-Glu-NCA at 0 8C was attempted. We reasoned the side reactions were considerably slower at this temperature.…”
Section: Resultsmentioning
confidence: 99%
“…However, although the ammonium halide mechanism is reported for the successful synthesis of hybrid block copolymers, no report has been found for the synthesis of block copolypeptides 36. Other methods exploit high vacuum and/or low temperature to optimize the conditions needed for a living polymerization 37, 38. During NCA polymerization under high vacuum, the carbamic groups and CO 2 are removed at a faster rate compared to when the reaction proceeds under atmospheric pressure.…”
Section: Synthetic Routes Toward Block Copolypeptides Via Nca Ropmentioning
confidence: 99%